The Effect of IFRS Adoption on the Readability of Annual Reports: An Empirical Study of Indonesian Public Companies - Irfan Hidayatullah; Dyah Setyaningrum (Institute of Research and Community Outreach - Petra Christian University, 2019)
This study aims to determine the effect of IFRS adoption on the readability of annual reports readability in Indonesia. The sample of this study includes 52 non-financial firms within a four-year period, from 2010-2011 and 2013-2014, with 208-year observations. Hypothesis testing is conducted by multiple linear regression analysis. This study provides evidence that IFRS adoption has significant and negative relationship with disclosure readability in Indonesian public companies. Implication of this study is IFRS adoption requires more sophisticated and/or more competent users of financial statements, measured by higher requirements of years of education needed to comprehend the disclosures.